Brain-computer interface (BCI) researcher perspectives on neural data ownership and privacy - Naufel, Stephanie; Klein, Eran (Journal of neural engineering, 2020)
Objective. Brain-computer interface (BCI) research and commercially available neural devices generate large amounts of neural data. These data have significant potential value to researchers and industry. Individuals from whose brains neural data derive may want to exert control over what happens to their neural data at study conclusion or as a result of using a consumer device. It is unclear how BCI researchers understand the relationship between neural data and BCI users and what control individuals should have over their neural data. Approach. An online survey of BCI researchers (n  =  122) gathered perspectives on control of neural data generated in research and non-research contexts. The survey outcomes are discussed and other relevant concerns are highlighted. Main results. The study found that 58% of BCI researchers endorsed giving research participants access to their raw neural data at the conclusion of a study. However, researchers felt that individuals should be limited in their freedom to either donate or sell these data. A majority of researchers viewed raw neural data as a kind of medical data. Survey respondents felt that current laws and regulations were inadequate to protect consumer neural data privacy, though many respondents were also unfamiliar with the details of existing guidelines. Significance. The majority of BCI researchers believe that individuals should have some but not unlimited control over neural data produced in research and non-research contexts.